Impact of atmospheric circulation on the rainfall-temperature relationship in Australia. (3rd September 2020) - Magan, Bhavik; Kim, Seokhyeon; Wasko, Conrad; Barbero, Renaud; Moron, Vincent; Nathan, Rory; Sharma, Ashish
Abstract: Anthropogenic climate change is leading to the intensification of extreme rainfall due to an increase in atmospheric water holding capacity at higher temperatures as governed by the Clausius-Clapeyron (C-C) relationship. However, the rainfall-temperature sensitivity (termed scaling) often deviates from the C-C relationship. This manuscript uses classifications prescribed by regional-scale atmospheric circulation patterns to investigate whether deviations from the C-C relationship in tropical Australia can be explained by differing weather types (WT). We show that the rainfall-temperature scaling differs depending on the WTs, with the difference increasing with rainfall magnitude. All monsoonal WTs have similar scaling, in excess of the C-C relationship, while trade winds (the driest WTs) result in the greatest scaling, up to twice that of the C-C relationship. Finally, we show the scaling for each WT also varies spatially, illustrating that both local factors and the WT will contribute to the behaviour of rainfall under warming.